Maternal vegetable intake during and after pregnancy - Alison Tovar; Jill L. Kaar; Karen McCurdy; Alison E. Field; Dana Dabelea; Maya Vadiveloo (BMC, 2019)
Abstract Background Improved understanding of vegetable intake changes between pregnancy and postpartum may inform future intervention targets to establish healthy home food environments. Therefore, the goal of this study was to explore the changes in vegetable intake between pregnancy and the postnatal period and explore maternal and sociodemographic factors that are associated with these changes. Methods We examined sociodemographic, dietary, and health characteristics of healthy mothers 18-43y from the prospective Infant Feeding Practices II cohort (n = 847) (2005-2012). Mothers completed a modified version of the diet history questionnaire, a food-frequency measure, developed by the National Cancer Institute. We created four categories of mothers, those that were: meeting vegetable recommendations post- but not prenatally (n = 121; improved intake), not meeting vegetable recommendations during pregnancy and postnatally (n = 370; stable inadequate), meeting recommendations pre- but not postnatally (n = 123; reduced intake), and meeting recommendations at both time points (n = 233; stable adequate). To make our results more relevant to public health recommendations, we were interested in comparing the improved vegetable intake group vs. stable inadequate vegetable intake group, as well as those that reduced their vegetable intake compared to the stable adequate vegetable intake group. Separate multivariable-adjusted logistic regression were used to examine sociodemographic predictors of improved vs. stable inadequate and reduced vs. stable adequate vegetable intake. Results Women with improved vegetable intake vs. stable inadequate smoked fewer cigarettes while women with reduced vegetable intake vs. stable adequate were more likely to experience less pregnancy weight gain. In adjusted models, employed women had greater odds of reduced vegetable intake (OR = 1.64 95% CI 1.14-2.36). In exploratory analyses, employment was associated with greater odds of reduced vegetable intake among low-income (OR = 1.79; 95% CI 1.03-3.1), but not higher income women (OR = 1.31; 95% CI 0.94-1.84). After further adjustment for paid maternity leave, employment was no longer associated with vegetable intake among lower income women (OR: 1.53; 95% CI: 0.76-3.05). Conclusions More women with reduced vs. stable adequate vegetable intake were lower income and worked full time. Improved access to paid maternity leave may help reduce disparities in vegetable quality between lower and higher income women.